Harnessing the power of the electronic health record for ALS research and quality improvement: CReATe CAPTURE‐ALS and the ALS Toolkit. Issue 2 (16th November 2021) - Granit, Volkan; Grignon, Anne‐Laure; Wuu, Joanne; Katz, Jonathan; Walk, David; Hussain, Sumaira; Hernandez, Jessica; Jackson, Carlayne; Caress, James; Yosick, Tom; Smider, Nancy; Benatar, Michael
Abstract: The electronic health record (EHR) is designed principally to support the provision and documentation of clinical care, as well as billing and insurance claims. Broad implementation of the EHR, however, also yields an opportunity to use EHR data for other purposes, including research and quality improvement. Indeed, effective use of clinical data for research purposes has been a long‐standing goal of physicians who provide care for patients with ALS, but the quality and completeness of clinical data, as well as the burden of double data entry into the EHR and into a research database, have been persistent barriers. These factors provided motivation for the development of the ALS Toolkit, a set of interactive digital forms within the EHR that enable easy, consistent, and structured capture of information relevant to ALS patient care (as well as research and quality improvement) during clinical encounters. Routine use of the ALS Toolkit within the context of the CReATe Consortium's institutional review board–approved Clinical Procedures to Support Research in ALS (CAPTURE‐ALS) study protocol, permits aggregation of structured ALS patient data, with the goals of empowering research and driving quality improvement. Widespread use of the ALS Toolkit through the CAPTURE‐ALS protocol will help to ensure that ALS clinics become a driving force for collecting and aggregating clinical data in a way that reflects the true diversity of the populations affected by this disease, rather than the restricted subset of patients that currently participate in dedicated research studies.